(untitled) (Research, Society and Development, 2021)
Shrimp residues have a high nutritional value and can be transformed into flour for human consumption, with feasibility of inclusion and enrichment of food products. The objective of this work was to develop instant soup based on shrimp flour, generating an alternative for the use of processing residue. Three different Amazon shrimp flours (Macrobrachium amazonicum) were prepared, with treatment 1 = whole Amazon shrimp flour (FCI), treatment 2 = whole Amazon shrimp flour cleaned (FCL) and treatment 3 = flour from the residue of the Whole Amazon Shrimp (FRC), which were included in instant soups, with subsequent characterization of proximate and sensory composition. The flours and soups were within microbiological standards. The clean shrimp meal had the highest crude protein content (87.32%) and the shrimp residue meal the highest levels of ash and carbohydrates, 22.59% and 17.06%, respectively. As for moisture and total lipids, there were no significant differences between the processed flours. The instant soup with FCL had the highest protein content (23.42%) and the lowest ash content (5.75%). But, in relation to sensory analysis, it was the soup with FRC inclusion that presented the best grades for the attributes aroma, global impression and purchase intention, while for the others there was no significant difference. Thus, the waste generated in the processing of shrimp can be used to prepare flours with high nutritional value, for inclusion in various food products commonly consumed by the population, such as instant soups.